A coverage-aware energy replenishment scheme for wireless rechargeable sensor networks - Kuei-Ping Shih; Chi-Ming Yang (EURASIP Journal on Wireless Communications and Networking, 2017)
Abstract Wireless rechargeable sensor networks are becoming crucial and important in recent years for the advancement of wireless energy transmission technology. The previous research showed that not all of sensors can be recharged due to the limitation of energy capacity that mobile chargers can carry. If a sensor playing a critical role in a sensing task cannot function as usual due to exhausted energy, then the sensing task will be interrupted. Therefore, this paper proposes a novel recharging mechanism taking the coverage of sensors into consideration such that mobile chargers can recharge the sensor with a high coverage degree and the network lifetime can be efficiently sustained. The coverage degree of each sensor depends on its contribution to the sensing task, including the coverage and connectivity capabilities. Based on the coverage degree, the sensor with a higher coverage degree will be properly recharged to extend the network lifetime. Simulation results show that the proposed mechanism performs better against the related work in network lifetime.